2019
DOI: 10.1177/0034523719882455
|View full text |Cite
|
Sign up to set email alerts
|

How does a sense of belonging develop in postsecondary? A conceptual Belonging in Academia Model (BAM) from sighted perspectives

Abstract: Belonging is associated with increased engagement in academic pursuits and well-being. However, there is a lack of research on how a sense of belonging develops in academia. The academic environment comprises largely of sighted individuals. Exploring sighted students, staff, and educators’ perceptions of belonging contributes to our understanding of environments that foster belonging for sighted individuals and their perceptions of the same for people who are blind. We conducted focus groups and in-depth inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…The results of this study agree with those of previous research in which the feeling of belonging has demonstrated positive effects on the intention to persist (Hausmann et al, 2007); on belonging and identification to reduce retention (Hoffmann et al, 2002); on academic selfefficacy; on intrinsic motivation and task value; on the promotion of student participation (Freeman et al, 2007); sense of belonging as a significant predictor of self-reported metacognitive and academic time management strategies (Won et al, 2018) and on belonging, familiarity, acceptance, and a sense of justice (Teng et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study agree with those of previous research in which the feeling of belonging has demonstrated positive effects on the intention to persist (Hausmann et al, 2007); on belonging and identification to reduce retention (Hoffmann et al, 2002); on academic selfefficacy; on intrinsic motivation and task value; on the promotion of student participation (Freeman et al, 2007); sense of belonging as a significant predictor of self-reported metacognitive and academic time management strategies (Won et al, 2018) and on belonging, familiarity, acceptance, and a sense of justice (Teng et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The barriers faced by students with VI in higher education may induce these students to make extra effort in order to succeed (Armstrong & Murray, 2007;Frank et al, 2020) and may negatively affect their emotional perceptions (Dunn, 2015;Palan, 2021). This can negatively affect visually impaired students' sense of belonging to the university (see Bishop & Rhind, 2011;Teng et al, 2020). Moreover, these types of barriers may cause students with VI to experience difficulty in completing their education, or even to leave the university (Hewett et al, 2017;Moriña, 2019).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Whereas belonging is clearly vital to promoting inclusion, culture change, and sustained post-secondary participation (Almog, 2018), it is important to understand how students create belonging. Based on their grounded theory study with sighted individuals, Teng et al (2020) proposed a conceptual model describing a process by which sense of belonging develops: the Belonging in Academia Model…”
Section: Bam: a Model Of Belongingmentioning
confidence: 99%
“…The researcher examined if data related to the BAM, and how blind/partially blind students' perspectives might contradict and build upon sighted individuals' perspectives reported in Teng et al (2020).…”
Section: Member Reflectionsmentioning
confidence: 99%